Hearst Magazines International. (A), George Green's 156 tips for long-lasting success - Rosenthal, Jean W., 1945-; Elias, Jaan; Dhar, Ravi ([London] : SAGE, 2016)
In 1989, George Green took over as the first head of Hearst Magazines International (HMI), a division founded to spearhead the Hearst publishing empire's forays outside the United States. Green started with a slim list of international titles, but under his direction HMI had expanded to 156 editions in 36 languages, distributed in over 100 countries. This study explains how Green achieved such success.
Originally Published in: Rosenthal, J. W., Elias, J., & Dhar, R. (2008). Hearst Magazines International (A): George Green's 156 Tips for Long-Lasting Success. 08-067. New Haven, CT: Yale School of Management, Yale University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Hearst Magazines International; International business enterprises -- Case studies; Strategic planning -- Case studies